(untitled) (Agrometeoros, 2022)
The objective of this study was to determine the accumulated degree-days (DD) to reach six plant developmental stages (PDS) of irrigated rice cultivars. Field experiments were carried out at the Estação Experimental Terras Baixas (ETB) of Embrapa Clima Temperado, located in the municipality of Capão do Leão, State of Rio Grande do Sul, Brazil, during 12 crop seasons, using six sowing dates in each. Ten plants of each cultivar were tagged and had each of the PDS monitored throughout the crop cycle. The DD (°C day) were calculated as the sum of the daily values resulting from the difference between mean air temperature (Tm) and the minimal base temperature (Tb = 11 °C), from the emergence until the date of each PDS. The results indicated that the DD to reach anthesis (R4) represented, in the average, about 77% of the total cycle (R9), ranging from 73% for IRGA 421 to 91% for Epagri 109. The vegetative period (from E-emergence to R1) is the one with the highest average DD value, around 48% of the total cycle, presenting also the largest differences between cultivars when compared to the reproductive period 1 (R1-R4) and the reproductive period 2 (R4-R9).